THE INFLUENCE OF PERCEPTIONS OF E-TRUST, E-WOM, AND WEB QUALITY TOWARDS ONLINE REPURCHASE INTENTION (Case Study in Tokopedia) - Saputra, Alvin Denis (Universitas Mercu Buana, 2021)
This research is to find out the Model on The Influence of Perceptions of e- Trust, e-WOM, and Web Quality Towards Online Repurchase Intention. The subjects in this study were college student in Mercu Buana who ever made transaction in Tokopedia site. The sample used in this study was 95 respondents. The sampling technique uses purposive sampling. By using a quantitative descriptive approach. Analysis of the data used is statistical analysis in the form of SEM-PLS. The results of this study indicate that e-Trust has a positive effect on Online Repurchase Intention. e- WOM has a significant positive effect on Online Repurchase Intention and Web Quality has a positive effect on Online Repurchase Intention.